Strategi Manajemen Konflik dalam Pengembangan Soft Skill dan Hard Skill Siswa Kelas 4 di SDI Full Day Baitul Izzi - Dindya Vikri Roemaissha; Alfian Wahidi; Ahmad Ansori (UIN Mahmud Yunus Batusangkar, 2023)
AbstractThis research is focused on explaining how conflict management strategies towards the development of soft skills and hard skills of 4th graders at SD I Full Day Baitul Izzi. This study used a qualitative approach with case study design. The data collection techniques used are observation, interviews, and documentation in collecting data. The results of the study there are several conflicts that occur in the development of soft skills and hars skills, including: a. Conflict in soft skill development; shift in norms caused by the times, the innate character possessed by students. b. Conflict in hard skill development; IQ difference, lazy to read and write. Several efforts have been made, namely: a. Conflict management strategy in soft skill development; using the class development method, becoming Uswatun Hasanah. b. Conflict strategy in hard skill development; provide additional hours for students who have low IQs, show children who are lazy to read to read while learning and record every material that has been explained for children who are lazy to write.